Opportunities and challenges in reducing personal inhalation exposure to air pollution among electronic waste recovery workers in Ghana. Issue 5 (1st February 2021) - Laskaris, Zoey; Batterman, Stuart A.; Arko‐Mensah, John; Mukherjee, Bhramar; Fobil, Julius N.; O'Neill, Marie S.; Robins, Thomas G.
Abstract: Background: Informal sector electronic waste (e‐waste) recovery produces toxic emissions resulting from burning e‐waste to recover valuable metals. Objectives: To identify high‐risk worker groups by measuring relative levels of personal inhalation exposure to particulate matter (PM) of fine (≤2.5 µm) and coarse (2.5–10 µm) fractions (PM2.5 and PM2.5–10, respectively) across work activities among e‐waste workers, and to assess how wind conditions modify levels of PM by activity and site location. Methods: At the Agbogbloshie e‐waste site, 170 partial‐shift PM samples and time‐activity data were collected from participants ( N  = 105) enrolled in the GeoHealth cohort study. Personal sampling included continuous measures of size‐specific PM from the worker's breathing zone and time–activity derived from wearable cameras. Linear mixed models were used to estimate changes in personal PM2.5 and PM2.5–10 associated with activities and evaluate effect modification by wind conditions. Results: Mean (±standard deviation) personal PM2.5 and PM2.5–10 concentrations were 80 (±   81) and 123 (± 139) µg m −3, respectively. The adjusted mean PM2.5 concentration for burning e‐waste was 88 µg m −3, a 28% increase above concentrations during non‐recovery activities (such as eating). Transportation‐related and burning activities were associated with the highest PM2.5–10 concentrations. Frequent changes in wind direction were associated with higher PM2.5 concentrations when burning, and high wind speeds with higher PM2.5–10 concentrations when dismantling e‐waste downwind of the burning zone.